2008
DOI: 10.14236/jhi.v16i1.673
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the MoleMateTM training program for assessment of suspicious pigmented lesions in primary care

Abstract: Background Pigmented skin lesions or 'moles' are a common presenting problem in general practice consultations: while the majority are benign, a minority are malignant melanomas. The MoleMate TM system is a novel diagnostic tool which incorporates spectrophotometric intracutaneous analysis (SIAscopy) within a non-invasive scanning technique and utilises a diagnostic algorithm specifically developed for use in primary care. The MoleMate TM training program is a short, computer-based course developed to train pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Wood et al 53 reported that a short, computer-based course significantly improved SIAscopic feature recognition in a group of 25 primary care providers, whose median test scores improved from 74% to 86% after training. Watson et al 54 In a large randomized controlled trial, Walter et al 55 studied the evaluation by primary care physicians of 1297 patients presenting with pigmented skin lesions that were not immediately diagnosed as benign.…”
Section: Regulation Of Mobile Technologiesmentioning
confidence: 99%
“…Wood et al 53 reported that a short, computer-based course significantly improved SIAscopic feature recognition in a group of 25 primary care providers, whose median test scores improved from 74% to 86% after training. Watson et al 54 In a large randomized controlled trial, Walter et al 55 studied the evaluation by primary care physicians of 1297 patients presenting with pigmented skin lesions that were not immediately diagnosed as benign.…”
Section: Regulation Of Mobile Technologiesmentioning
confidence: 99%
“…The MoleMate system incorporates the SIAscope device with a diagnostic algorithm for primary care physicians to use. Its efficacy is currently under investigation [30-32]. For optimal use, the SIAscope requires experienced users who can accurately interpret SIAscope images.…”
Section: Multispectral Imagingmentioning
confidence: 99%
“…When used by primary care physicians, SIAscope has a sensitivity of 94%, with a false negative rate of 4% [28]. In the UK and Australia, a scoring algorithm was recently developed, tailored to primary care physicians using SIAscope [32,33]. Additional studies evaluating the efficacy of these protocols are underway.…”
Section: Use Of Imaging Modalities By Primary Care Physicians For Melmentioning
confidence: 99%
“…The issue contains a number of thought provoking articles about what influences the uptake of IT, 1 how it can catalyse change 2 and our expectations for the next generation of electronic patient records 3 as well as insights into how computerised decision support 4,5 and access grid technologies (high powered video conferencing) can facilitate primary care research. 6 A recent international consensus conference described current initiatives and barriers to developing primary care IT: The papers in this edition reinforce these themes, but offer new thoughts about the use and deployment of IT and also raise whether we should once again consider better problem orientation of records?…”
mentioning
confidence: 99%
“…It is possible that the more structured and codified nature of the computerised record has led to a greater orientation The next two papers in this edition look at the use of computerised decision support systems (CDSS): the first of these to improve the management of heart failure 4 and the second at the role of training to improve the accuracy of a new technology (called spectrophotometric intracutaneous analysis -SIA) to identify malignant melanomata (cancerous skin lesions). 5 The issue of training is important within informatics as for some technologies (e.g. mobile phones) none is provided; for many EPR systems little is provided and we need to develop an evidence base as to whether such investment is likely to achieve a return in quality of care and patient safety.…”
mentioning
confidence: 99%